Longitudinal Impact of the myPlan App on Health and Safety Among College Women Experiencing Partner Violence - Glass, Nancy E.; Clough, Amber; Messing, Jill T.; Bloom, Tina; Brown, Megan Lindsay; Eden, Karen B.; Campbell, Jacquelyn C.; Gielen, Andrea; Laughon, Kathryn; Grace, Karen Trister; Turner, Rachael M.; Alvarez, Carmen; et al. (Journal of interpersonal violence, 2022)
The objective of this study was to examine differences in change over time in health and safety outcomes among female college students randomized to myPlan, a tailored safety planning app, or usual web-based safety planning resources. Three hundred forty-six women (175 intervention, 171 control) from 41 colleges/universities in Oregon and Maryland completed surveys at baseline, 6- and 12-months from July 2015 to October 2017. Generalized estimating equations were used to test group differences across time. Both groups improved on four measure of intimate partner violence (IPV; Composite Abuse Scale [CAS], TBI-related IPV, digital abuse, reproductive coercion [RC]) and depression. Reduction in RC and improvement in suicide risk were significantly greater in the myPlan group relative to controls (p = .019 and p = .46, respectively). Increases in the percent of safety behaviors tried that were helpful significantly reduced CAS scores, indicating a reduction in IPV over time in the myPlan group compared to controls (p = .006). Findings support the feasibility and importance of technology-based IPV safety planning for college women. myPlan achieved a number of its objectives related to safety planning and decision-making, the use of helpful safety behaviors, mental health, and reductions in some forms of IPV.